Survey of use of herbal and home remedies for hair and scalp among women in North West Saudi Arabia - Abdullah Alyoussef (PAGEPress Publications, 2020)
Herbal products and home remedies, especially those used as cosmetics, are widely used worldwide. Therefore, we conducted this study to discover the pattern of use of remedies in treating hair and scalp disorders in Tabuk, North West area of Saudi Arabia. A survey about use of herbal products and home remedies was prepared to evaluate their in hair and scalp. The questionnaire was distributed to 149 female hairdressers, hair products sellers and traditional healers as well as female customers in these places. We found about forty-one plants and eleven home remedies used for hair and scalp in Tabuk area. The most widely used plants were Henna (15.01%), coconut (10.22%) and olive (8.14%). They were widely used in hair damage (32.01%), hair endings (21.95%) and hair loss (21.94%). In parallel, the most widely used home remedies were yogurt (32.42%), eggs (26.91%) and honey (23.85%). They were widely used in hair damage (45.57%), hair endings (26.91%) and hair loss (19.88%). There were no differences between participants in the pattern of use of remedies regarding their education level of age group. In conclusion, many natural herbal medicine and home remedies are still in use in North West region of Saudi Arabia for hair and scalp. There is a great shortage in medical sources of information. Finally, many of used remedies lacks important scientific information about their usage and safety.